INCIDENCE OF BRONCHIAL ASTHMA SYMPTOMS IN CHILDREN IN DUSHANBE - D.S. Umarov; M.A. Gaffarova (Union of pediatricians of Russia, 2008)
The article presents the research results of school aged children in dushanbe according to isaac (international study of asthma and allergy in childhood) program protocol, which is an international research of bronchial asthma and allergy symptoms in children.Key words: bronchial asthma, epidemiology, children.